Orofacial pain during the new coronavirus infection (COVID-19) pandemic - Dmitry I. Trukhan; Anatoly F. Sulimov; Larisa Yu. Trukhan; Innokenty S. Chusov; Igor N. Stepanov (LLC "MEDIAFORMAT", 2022)
Doctors of various specialties face orofacial pain in their practice: dentists, maxillofacial surgeons, neurologists, otorhinolaryngologists, therapists, traumatologists, ophthalmologists, psychotherapists, physiotherapists, aesthetic medicine doctors, neurosurgeons, anesthesiologists, plastic surgeons and other specialists. The novel coronavirus infection (COVID-19) pandemic, spread by the SARS-CoV-2 virus, has become a challenge for all medical specialties and health care systems around the world. We searched the literature for the period from the beginning of the pandemic until June 15, 2022, on the study of the association of orofacial pain with a new coronavirus infection COVID-19 in the electronic search engines PubMed and Scopus. An analysis of the sources found indicates an increase in the frequency of various types of orofacial pain during the COVID-19 pandemic, which is due both to the SARS-CoV-2 infection itself and to a complex of biopsychosocial factors directly related to the pandemic. A number of used drugs, primarily non-steroidal anti-inflammatory drugs, can cause a number of side effects that complicate both dental treatment and negatively affect concomitant comorbid pathology. In this regard, the issues of drug safety and pharmacological "correction" of side effects - protective or protector therapy - become relevant. The use of the universal gastro- and enteroprotector rebamipide is especially important during the pandemic of a new coronavirus infection (COVID-19).